The Future of Voluntary Hospital Contributory Schemes - The point of view of the wage earning community / by H. H. Elvin - Elvin, Herbert Henry
1938-12-14 1938 1930s 7 pages PRIVATE AND CONFIDENTIAL Soc.Ins.C'tee.3/1. 14th Dec., 1938. TRADES UNION CONGRESS THE FUTURE OF VOLUNTARY HOSPITAL CONTRIBUTORY SCHEMES - THE POINT OF VIEW OF THE WAGE EARNING COMMUNITY. By H.H.. Elvin. Health, Illness and Treatment are of prime importance to the worker. There is the general question that without good health life cannot be enjoyed. Even the rich dyspeptic find his trouble inconvenient and a bar to full enjoyment. But he has other compensating advantages denied to the working man. There is another aspect: the health of the worker is his capital in a very real sense. It is generally accepted that he has to sell his labour to secure his bread, but it is not generally appreciated that the value of his labour depends very largely upon the state of his health. Many workers suffer a double handicap. By the circumstances of their birth and childhood they are handicapped in their future life. Others, born healthy, are weakened by privation, and their development is hampered. But whether they enter upon manhood physically fit or lesser fit, all the time they are at work they are expending their capital (and when out of work their capital wastes), and as each year passes on, their physical reserves are such that they are not able to stand the strain; and owing to the further handicap that their economic existence has been one continuous struggle to live they either break up completely long before they should, or become a burden in their declining years upon others - against which they chafe, because the burden, although willingly shouldered by others, adds to the difficulties of the burden bearers. Of course, those who belonged to their Trade Unions or Friendly Societies are better off than those who were not; but the general position has been improved somewhat by the development of national social services, which have contributed considerably to the health of the people. There are, however, still many gaps, and it was with considerable alarm that the country heard of the threat of a Cabinet Minister that, notwithstanding the terrible position in which millions of our fellow-citizens find themselves to-day because of economic need, these social services were likely to be cut into, and was relieved when it was subsequently announced that this was not to be so. The gap that I have particularly in mind is that of complete preventive and curative treatment of diseases. It is this gap that the Voluntary Hospitals system of this country seeks to deal with. 292/842/2/220